Effects of dapagliflozin on volume status and systemic haemodynamics in patients with chronic kidney disease without diabetes: Results from DAPASALT and DIAMOND. Issue 8 (1st June 2022) - Sen, Taha; Scholtes, Rosalie; Greasley, Peter J.; Cherney, David Z. I.; Dekkers, Claire C. J.; Vervloet, Marc; Danser, Alexander H. J.; Barbour, Sean J.; Karlsson, Cecilia; Hammarstedt, Ann; Li, Qiang; Laverman, Gozewijn D.; et al.
Abstract: Aims: To assess the effect of sodium‐glucose cotransporter‐2 inhibitor dapagliflozin on natriuresis, blood pressure (BP) and volume status in patients with chronic kidney disease (CKD) without diabetes. Materials and methods: We performed a mechanistic open‐label study (DAPASALT) to evaluate the effects of dapagliflozin on 24‐hour sodium excretion, 24‐hour BP, extracellular volume, and markers of volume status during a standardized sodium diet (150 mmol/d) in six patients with CKD. In parallel, in a placebo‐controlled double‐blind crossover trial (DIAMOND), we determined the effects of 6 weeks of dapagliflozin on markers of volume status in 53 patients with CKD. Results: In DAPASALT (mean age 65 years, mean estimated glomerular filtration rate [eGFR] 39.4 mL/min/1.73 m 2, median urine albumin:creatinine ratio [UACR] 111 mg/g), dapagliflozin did not change 24‐hour sodium and volume excretion during 2 weeks of treatment. Dapagliflozin was associated with a modest increase in 24‐hour glucose excretion on Day 4, which persisted at Day 14 and reversed to baseline after discontinuation. Mean 24‐hour systolic BP decreased by −9.3 (95% confidence interval [CI] −19.1, 0.4) mmHg after 4 days and was sustained at Day 14 and at wash‐out. Renin, angiotensin II, urinary aldosterone and copeptin levels increased from baseline. In DIAMOND (mean age 51 years, mean eGFR 59.0 mL/min/1.73 m 2, median UACR 608 mg/g), compared to placebo, dapagliflozin increased plasma renin (38.5 [95% CI 7.4, 78.8]%), aldosterone (19.1 [95% CI −5.9, 50.8]%), and copeptin levels (7.3 [95% CI 0.1, 14.5] pmol/L). Conclusions: During a standardized sodium diet, dapagliflozin decreased BP but did not increase 24‐hour sodium and volume excretion. The lack of increased natriuresis and diuresis may be attributed to activation of intra‐renal compensatory mechanisms to prevent excessive water loss.